Primary recovery factor as a function of production rate: implications for conventional reservoirs with different drive mechanisms. Issue 22 (17th November 2019) - Raza, Arshad; Gholami, Raoof; Wheaton, Richard; Rabiei, Minou; Rasouli, Vamegh; Rezaee, Reza
ABSTRACT: This study evaluates the dependency of production rate on the recovery of hydrocarbon from conventional reservoirs using MBAL simulator. The results indicated that the recoveries are sensitive to the production rate in almost all hydrocarbon reservoirs. It was also found that the recovery of volumetric gas drive reservoirs is not impacted by the production rate. In fact, any increase in the production rate improves gas recovery in weak and strong water drive reservoirs. Moreover, increasing the production rate in oil reservoirs decreases the recovery with a significant effect observed in the weak water drive reservoirs. The results of this study demonstrate the need for implementing an effective reservoir management in order to obtain a maximum recovery.